Vito Acconci. Spaces of Play - Monica Manolescu (Transatlantica)
This article offers an investigation of Vito Acconci’s writings and art from the point of view of play, understood as game and performance. Various examples are analyzed, both literary and artistic (early texts, the emblematic Following Piece, which was one of the earliest examples of performance art, and The American Gift, combining sound and sculpture in a museum space). Acconci strikes a balance between freedom and constraint, playing with existing models according to set protocols in game-like fashion and offering a constantly renewed artistic practice.